2018
DOI: 10.1111/desc.12672
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time lexical comprehension in young children learning American Sign Language

Abstract: When children interpret spoken language in real time, linguistic information drives rapid shifts in visual attention to objects in the visual world. This language-vision interaction can provide insights into children's developing efficiency in language comprehension. But how does language influence visual attention when the linguistic signal and the visual world are both processed via the visual channel? Here, we measured eye movements during real-time comprehension of a visual-manual language, American Sign L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…That said, the sample size for DoD infants was comparable in size to other prominent studies of language processing and social cognition with DoD children (e.g. MacDonald et al, 2018;Peterson et al, 2005) and other low-incidence populations (e.g. Williams Syndrome: Hocking et al, 2013;Järvinen et al, 2015;blind children: Iverson, 1999;Landau et al, 1981).…”
Section: Limitations Future Directions and Broader Theoretical Immentioning
confidence: 74%
See 1 more Smart Citation
“…That said, the sample size for DoD infants was comparable in size to other prominent studies of language processing and social cognition with DoD children (e.g. MacDonald et al, 2018;Peterson et al, 2005) and other low-incidence populations (e.g. Williams Syndrome: Hocking et al, 2013;Järvinen et al, 2015;blind children: Iverson, 1999;Landau et al, 1981).…”
Section: Limitations Future Directions and Broader Theoretical Immentioning
confidence: 74%
“…Hypothesis-3 holds that Deaf parents actively engage in specific communicative and linguistic behaviors that are highly adaptive in the Deaf culture and may scaffold gaze-following development (Corina & Singleton, 2009;Harris, 2000;Lieberman, Hatrak, & Mayberry, 2011;Meadow-Orlans et al, 2004;Spencer, 2000). behavior is also suggested in a study of the real-time comprehension of sign-language stimuli by older infants (MacDonald et al, 2018). In that study, both Deaf and hearing ASL-exposed infants demonstrated similar eye gaze patterns, including rapid gaze-shifting ability.…”
Section: Discussionmentioning
confidence: 99%
“…To measure relative differences in target fixations as a function of competitor type, we analyzed fixations to the target picture over a broad time window that began at the offset of the target sign and continued for 1,500 milliseconds (Figure 4). Similar time windows have been used in previous studies of lexical processing in sign language (Lieberman et al., 2015; MacDonald et al., 2018). We log transformed target to competitor looking ratio using the formula log10(target fixations/competitor fixations).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, MacDonald et al. (2018) probed sign recognition in deaf toddlers (ages 16 to 53 months), using a technique similar, though not identical, to ours. The definition of sign onset in Macdonald et al.’s study was somewhat different from the one used in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation